Improvement and implementation of a national individual care plan in paediatric palliative care: a study protocol. Issue 1 (25th January 2023) - Joren, Chantal Y; Kars, Marijke C; Kremer, Leontien C M; Rippen, Hester; Verhagen, A A Eduard; Aris-Meijer, Judith L
Abstract : Introduction: Paediatric palliative care (PPC) is care for children with life-threatening or life-limiting conditions, and can involve complex high-tech care, which can last for months or years. In 2015, the National Individual Care Plan (ICP) for PPC was developed and has shown to be successful. The ICP can be seen as an instrument to facilitate coordination, quality and continuity of PPC. However, in practice, an ICP is often completed too late and for too few children. We aim to improve the coordination, quality and continuity of care for every child with a life-threatening or life-limiting condition and his/her family by further developing and implementing the ICP in the Netherlands. Methods and analysis: To evaluate the original ICP, ICP 1.0, interviews and questionnaires will be held among parents of children who have or have had an ICP 1.0 and healthcare professionals (HCPs) who used ICP 1.0. Based on the results, ICP 1.0 will be further developed. An implementation strategy will be written and the renewed ICP, ICP 2.0, will be nationally tested in an implementation period of approximately 7 months. During the implementation period, ICP 2.0 will be used for all children who are registered with Children's Palliative Care teams. After the implementation period, ICP 2.0 will be evaluated using interviews and questionnaires among parents of children who received ICP 2.0 and HPCs who worked with ICP 2.0. Based on these results, ICP 2.0 will be further optimised into the final version: ICP 3.0. Ethics and dissemination: This study received ethical approval. The ICP 3.0 will be disseminated through the Dutch Centre of Expertise in Children's Palliative Care, to ensure wide availability for the general public and HCPs within PPC. Additionally, we aim to publish study results in open-access, peer-reviewed journals and to present results at national and international scientific meetings.